2020
DOI: 10.3389/fgene.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

MED12-Related Disease in a Chinese Girl: Clinical Characteristics and Underlying Mechanism

Abstract: The RNA polymerase II transcription subunit 12 homolog (MED12) is a member of the mediator complex, which plays a critical role in RNA transcription. Mutations in MED12 cause X-linked intellectual disability and other anomalies collectively grouped as MED12related disorders. While MED12 mutations have been most commonly reported in male patients, we present the case of a 1-year-old girl with clinical characteristics similar to MED12-related disorders. To explore the clinical characteristics of the condition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…15 Secondly, a de novo splice variant that is identical to the one identified in individual 1 in this study, was reported in a one year old female with a similar phenotype comprising developmental delay, facial dysmorphism, cleft lip and palate and a thin corpus callosum. 31 For the two novel splice-variants we identified, we could not detect an aberrant transcript.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…15 Secondly, a de novo splice variant that is identical to the one identified in individual 1 in this study, was reported in a one year old female with a similar phenotype comprising developmental delay, facial dysmorphism, cleft lip and palate and a thin corpus callosum. 31 For the two novel splice-variants we identified, we could not detect an aberrant transcript.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly to previously reported missense variants found in males, the de novo missense variants identified in females in this study were distributed all over the protein. Previously, only two missense variants, p.(Glu172Gln) 29 and p.(Arg521His), 31 have been reported in females with comparable phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The girl showed clinical features very similar to those affected from Opitz-Kaveggia and Lujan syndrome (macrocephaly, dysgenesis of the corpus callosum, hypotonia, development delay, long and thin face, hyper nasal voice, high nasal root, repaired cleft lip and palate, short philtrum, and hyperextensible digits). The mutation lead to deregulated sonic hedgehog signalling which might have caused the diseased phenotype(Wang et al, 2020).4.1.2 | Ohdo syndrome, Maat-Kievit-Brunner typeThe Maat-Kievit-Brunner type of intellectual disability is a kind of mental retardation that happens usually in males and is X chromosome linked. Other than intellectual disability, certain physical features are typical of the disease and includes narrowing of the eye opening, droopy eyelids, prominent cheeks, broad nasal bridge, nose with a rounded tip, large space between the nose and upper lip, and a narrow mouth.…”
mentioning
confidence: 99%
“…Interestingly, the X‐chromosome inactivation profile in blood cells from the two sisters showed no correlation with clinical outcomes as previously reported in symptomatic female carriers of an X‐linked disease 8 . Likewise, an intronic splice variant causing exon 9 skipping in MED12 was recently reported in a girl with generalized hypotonia, cleft lip and palate, facial dysmorphism and pulmonary stenosis 9 . The clinical spectrum of MED12‐related disorders was further expanded when de novo loss of function variants in MED12 was shown to be associated with Hardikar syndrome (OMIM 612726) in females 10 .…”
Section: Introductionmentioning
confidence: 60%